Effects of Age-Related Stereotype Threat on Metacognition - Fourquet, Natasha Y.; Patterson, Tara K.; Li, Changrui; Castel, Alan D.; Knowlton, Barbara J. (Frontiers in Psychology, 2020)
Previous work has shown that memory performance in older adults is affected by activation of a stereotype of age-related memory decline. In the present experiment, we examined whether stereotype threat would affect metamemory in older adults; that is, whether under stereotype threat they make poorer judgments about what they could remember. We tested older adults (MAge = 66.18 years) on a task in which participants viewed words paired with point values and “bet” on whether they could later recall each word. If they bet on and recalled a word, they gained those points, but if they bet on and failed to recall a word, they lost those points. Thus, this task required participants to monitor how much they could remember and prioritize high value items. Participants performed this task over six lists of items either under stereotype threat about age-related memory decline or not under stereotype threat. Participants from both groups performed similarly on initial lists, but on later lists, participants under stereotype threat showed impaired performance as indicated by a lower average point score and a lower average gamma coefficient. The results suggest that a modest effect of stereotype threat on recall combined with a modest effect on metacognitive judgments to result in a performance deficit. This pattern of results may reflect an effect of stereotype threat on executive control reducing the ability to strategically use memory.